PREPARASI DAN KARAKTERISASI KOMPLEKS KITOSAN HIDROGEL-TEMBAGA(II) - Risfidian Mohadi; Nurlisa Hidayati; Melany N.R (Universitas Jenderal Soedirman, 2007)
Research about preparation and characterization complex of chitosan hydrogel–copper(II) had been done. Chitosan hydrogel was obtained from deacetylation of chitin which was isolated from crab shells. Characterization included determination of N-total, Corganic , deacetylation degree, and FTIR spectroscopy. The results of research showed that obtained chitosan had 7,9571% N-total, 2,767% Corganic, and 71,486% deacetylation degree. FTIR spectrum of chitosan showed the increasing in percentage of transmitant from C=O group and the shifting in wavenumber from 1561,5 to 1563 cm-1 indicated N-H bending. Generally, FTIR spectrum of chitosan hydrogel showed the shifting to higher wavenumbers caused by changing in bond angles of chitosan group. FTIR spectrum of chitosan hydrogel-copper(II) complex showed that absorption regions of N-H group becoming wide and the shifting in wavenumber from 1594,74 to 1542,9 cm-1 whichindicated N-H bending because of copper(II) bonding to N-group of chitosan.